Nursing interventions in stoma reversal: an integrative review - Gómez Barriga , Norma; Medina Garzón, Mauricio (Revista Cuidarte, 2021)
Introduction: Intestinal stomas have a significant impact on people’s quality of life. However, these should be reversed after gastrointestinal transit has been restored or the initial inflammatory response has gone. In addition, patients may refuse to reverse them due to a lack of information and guidance from healthcare professionals. Therefore, it is important to identify nursing interventions in caring for patients with stoma reversal. Materials and Methods: An integrative literature review was conducted in WOS, PubMed, Scopus, SciELO and Cochrane databases published between 2015 and 2020. 36 articles were selected based on inclusion and exclusion criteria with their methodological analysis. Results: The following nursing interventions were identified: preoperative assessment, bowel preparation and follow-up of comorbidities in the preoperative period; prophylaxis, skin preparation, surgical technique and abdominal wall closure in the intraoperative period; surgical wound care, quality of life and education in the postoperative period. Discussion: It is essential to reflect on reversal time, surgical technique and the importance of nursing interventions. Conclusions: Nursing plays an important role in stoma reversal not only because of physical care and education provided, but also the interventions applicable to social and emotional contexts affecting the patient’s lifestyle. How to cite this article: Gómez Barriga Norma Yaneth, Medina Garzón Mauricio. Intervenciones de Enfermería en la reversión del estoma intestinal: revisión integrativa. Revista Cuidarte. 2022;13(1):e2165. http://dx.doi.org/10.15649/cuidarte.2165